Results of preoperative electrical stimulation of pelvic floor muscles in the continence status following radical retropubic prostatectomy - Laurienzo,Carla Elaine (2013)
Purpose To evaluate preoperative rectal electrical stimulation in the recovery of urinary continence in patients who undergo radical retropubic prostatectomy. Materials and Methods Patients were divided into 3 randomized groups: control, pelvic exercises, and electrical stimulation. A 1 hour pad-test, the ICIQ-SF, and the SF-36 were performed 1, 3, and 6 months after the surgical procedure. Results Of the 58 patients who were initially included in the study, 9 were excluded due to radiotherapy after surgical intervention, an indwelling urethral catheter for more than 30 days, high surgical risk, loss of follow-up, or incomplete participation in the study routines and spontaneous interruption. Forty-nine patients concluded the study (15 in the control group, 17 in the exercise group, and 17 in the electrical stimulation group). We did not observe any significant difference in the pad test (p > 0.05), the 8 domains of the SF-36, or ICIQ-SF score compared with control groups (control, exercise, and electrical stimulation). Conclusion Preoperative rectal electrical stimulation has no impact on continence status in patients who undergo radical retropubic prostatectomy. There is no difference in the three above mentioned groups with regard to urinary leakage and quality of life.